Correlation between fms-Like Tyrosine Kinase-1 (sFlt-1) Cell-Free Messenger RNA Expression and fms-Like Tyrosine Kinase-1 (sFlt-1) Protein Level in Severe Preeclampsia and Normal Pregnancy - Jeffry Iman Gurnadi; Johanes Cornelius Mose; Budi Handono; Prima Nanda Fauziah; Akhmad Yogi Pramatirta (International Journal of Integrated Health Sciences, 2015)
Objective: Preeclampsia is still a problem in Indonesia due to the high maternal and neonatal morbidity and mortality. Placental soluble fms-like tyrosine kinase-1 (sFlt-1), an antagonist of vascular endothelial growth factor (VEGF), and placental growth factor (PIGF), is considered as one of the etiology factors that cause endothelial damage in preeclampsia due to increased sFlt-1 level modulating vascular endothelial integrity. This study aims to analyze sFlt-1 and sFlt-1 mRNA levels in severe preeclampsia and normal pregnancy, and the correlation between both in occurrence of severe preeclampsia.Methods: This is a cross-sectional analytic observational study involving 18 subjects with severe preeclampsia and 19 subjects with normal pregnancy as controls who met inclusion and exclusion criteria. Levels of sFlt-1 and sFlt-1 mRNA were measured with ELISA and RT PCR. Statistical analysis was performed with Chi square test, Fisher’s exact test, T-test, Mann-Whitney test, and Spearman’s rank correlation test.Results: This study showed no significant difference (p>0.05) in characteristics of maternal age, gestational age, and parity in both study groups. Mean level of sFlt-1 mRNA in severe preeclampsia was higher (6.3404 pg/mL) compared to its level in normal pregnancy (5.9701 pg/mL). There is a not significant (p>0.05) positive correlation between sFlt-1 mRNA with sFlt-1 level in normal pregnancy, and a not significant (p>0.05) negative correlation between both level in severe preeclampsia.Conclusions: sFlt-1 mRNA levels in severe preeclampsia are higher than its level in normal pregnancy. There is no correlation between sFlt-1 mRNA level and sFLt-1 protein level in severe preeclampsia. There is a not significant positive correlation between sFlt-1 mRNA with sFlt-1 level in normal pregnancy, and a not significant negative correlation between both in severe preeclampsia.Keywords: Normal pregnancy, severe preeclampsia, sFlt-1 mRNA DOI: 10.15850/ijihs.v3n2.586